Biocuration of functional annotation at the European nucleotide archive. Issue Volume 44:Issue D1(2016) (28th November 2015) - Gibson, Richard; Alako, Blaise; Amid, Clara; Cerdeño-Tárraga, Ana; Cleland, Iain; Goodgame, Neil; ten Hoopen, Petra; Jayathilaka, Suran; Kay, Simon; Leinonen, Rasko; Liu, Xin; Pallreddy, Swapna; et al.
Abstract: The European Nucleotide Archive (ENA; http://www.ebi.ac.uk/ena ) is a repository for the submission, maintenance and presentation of nucleotide sequence data and related sample and experimental information. In this article we report on ENA in 2015 regarding general activity, notable published data sets and major achievements. This is followed by a focus on sustainable biocuration of functional annotation, an area which has particularly felt the pressure of sequencing growth. The importance of functional annotation, how it can be submitted and the shifting role of the biocurator in the context of increasing volumes of data are all discussed.